MiRNA 34a: a therapeutic target for castration-resistant prostate cancer. (1st September 2016) - Chalanqui, Marine J.; O'Doherty, Michelle; Dunne, Nicholas J.; McCarthy, Helen O.
ABSTRACT: Introduction : Development of a therapy for bone metastases is of paramount importance for castration-resistant prostate cancer (CRPC). The osteomimetic properties of CRPC confer a propensity to metastasize to osseous sites. Micro-ribonucleic acid (miRNA) is non-coding RNA that acts as a post-transcriptional regulator of multiple proteins and associated pathways. Therefore identification of miRNAs could reveal a valid third generation therapy for CRPC. Areas covered : miR34a has been found to play an integral role in the progression of prostate cancer, particularly in the regulation of metastatic genes involved in migration, intravasation, extravasation, bone attachment and bone homeostasis. The correlation between miR34a down-regulation and metastatic progression has generated substantial interest in this field. Expert opinion : Examination of the evidence reveals that miR34a is an ideal target for gene therapy for metastatic CRPC. We also conclude that future studies should focus on the effects of miR34a upregulation in CRPC with respect to migration, translocation to bone micro-environment and osteomimetic phenotype development. The success of miR34a as a therapeutic is reliant on the development of appropriate delivery systems and targeting to the bone micro-environment. In tandem with any therapeutic studies, biomarker serum levels should also be ascertained as an indicator of successful miR34a delivery.